Polymer viscosifier for coal rock gas well and preparation method thereof

CN122541643BActive Publication Date: 2026-09-25GUANGRAO LIUHE CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611050032.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-09-25
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

[0008]针对现有煤岩气井用聚合物增粘剂存在的抗剪切性能有限、低温溶解效率不足、滤失控制能力有限及批次稳定性有待改善等问题,本发明提供一种煤岩气井用聚合物增粘剂及其制备方法

Benefits of technology

(1)本发明通过ABA型分段结构设计,使疏水缔合基团在链段末端富集,形成可逆物理交联网络,在170s⁻¹连续剪切120min后黏度保留率达85%以上,较常规无规共聚产品(62.3%)显著提升,且剪切后黏度恢复速度更快,更适配大排量体积压裂工况;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122541643B_ABST
    Figure CN122541643B_ABST
Patent Text Reader

Abstract

The application discloses a polymer tackifier for coal rock gas wells and a preparation method thereof, and belongs to the technical field of high polymer materials for gas well reconstruction. The preparation method adopts a double-functionality water-soluble RAFT reagent and a sequential two-step water solution polymerization process. First, a B-section monomer water solution is prepared and oxygen is removed, then the RAFT reagent is added for B-section pre-polymerization, and then the A-section monomer is added dropwise for A-section sequential polymerization, and finally, a water-soluble copolymer with an ABA type segmented structure characteristic is obtained through post-processing. The application realizes the segmented enrichment of associated groups through the design of the ABA segmented structure to improve the shear recovery performance, improves the low-temperature solubility performance through the methyl side group regulation, and enhances the interface adsorption through the polyoxyethylene ether side chain to improve the fluid loss reduction performance. The three synergistically improve the performance, while the good salt resistance, temperature resistance and batch stability are maintained, and the process is controllable, the performance is synergistically improved, and the industrial preparation is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology for gas well modification, and more specifically, relates to a polymer thickener for coal and rock gas wells and its preparation method. Background Technology

[0002] Coalbed methane reservoirs typically exhibit characteristics such as low porosity, low permeability, strong heterogeneity, sensitivity to clay minerals, and high formation water salinity. Hydraulic fracturing is a crucial technology for achieving efficient coalbed methane development. Polymer thickeners are key components in water-based fracturing fluids. Their main function is to increase the system viscosity through molecular hydration, chain extension, and intermolecular interactions, thereby enabling sand-carrying fracturing, reducing filtration loss, and improving operational stability.

[0003] However, existing polymer thickeners for coal and rock gas wells still have the following shortcomings: 1. Limited shear resistance: When hydrophobic or associating groups are randomly distributed on the chain, weak association points are easily formed in the system. Under high discharge conditions, the network structure is more prone to dissociation, and the viscosity retention and post-shear recovery capabilities need to be improved.

[0004] 2. Insufficient low-temperature dissolution efficiency: Under low-temperature conditions, polyacrylamide materials may experience slower dissolution rates, localized agglomeration, or uneven solution preparation due to decreased chain segment mobility and enhanced intermolecular interactions, thus affecting on-site preparation efficiency.

[0005] 3. Limited filtration control capability: The interfacial interaction between conventional viscosifiers and the coal and rock surface is usually weak. The retention and coverage capabilities of fracturing fluid at the coal and rock interface are limited, which may lead to increased liquid phase intrusion and is not conducive to reservoir protection.

[0006] Therefore, it is necessary to develop a polymer thickener for coal gas wells that has synergistic effects in improving shear resistance, low-temperature dissolution, filtration loss reduction, and salt resistance, as well as its preparation method. Summary of the Invention

[0007] 1. The problem to be solved

[0008] To address the problems of limited shear resistance, insufficient low-temperature dissolution efficiency, limited filtration control, and the need to improve batch stability of existing polymer thickeners for coal and rock gas wells, this invention provides a polymer thickener for coal and rock gas wells and its preparation method.

[0009] 2. Technical Solution

[0010] To solve the above problems, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing a polymer thickener for coal and rock gas wells. The method uses a bifunctional water-soluble RAFT reagent combined with a sequential two-step aqueous solution polymerization process to prepare a water-soluble copolymer with ABA-type segmented structure characteristics, wherein the middle B segment is a flexible hydrophilic segment and the two ends A segments are hydrophobic or weakly hydrophobic segments enriched with associating groups. The preparation method includes the following steps: (1) Preparation and deoxygenation of reaction system: Weigh out the monomers of section B according to the ratio, namely 65%~75% of the total monomer amount of acrylamide, all allyl polyoxyethylene ether and all methacrylamide, add them to deionized water and stir until completely dissolved to prepare an aqueous solution with a total monomer mass fraction of 25%~30%; adjust the pH of the system to 6.5~7.5 with a 20% sodium hydroxide solution; transfer the aqueous phase into a closed reaction vessel with a jacket and temperature control, and introduce high-purity nitrogen to deoxygenate for 20~30 min, maintaining a slight positive pressure of nitrogen; wherein, the total mass of acrylamide is 60~70 parts, the mass of allyl polyoxyethylene ether is 5~12 parts and the molecular weight is 800~2000, the mass of methacrylamide is 1~3 parts, and the slight positive pressure of nitrogen is 0.01~0.05 MPa; (2) Flexible hydrophilic B-segment prepolymerization: Add a bifunctional water-soluble RAFT reagent to the reactor, the amount of which is 0.03%~0.08% of the total monomer molars. Control the system temperature at 28~32℃. Add the first part of the redox initiator, the amount of which is 30%~40% of the total initiator mass. The total initiator amount is 0.02% of the total monomer mass. Keep the reaction at the temperature for 1.5~2.5h to obtain a B-segment prepolymer with chain end activity characteristics. The bifunctional water-soluble RAFT reagent is bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate. (3) Hard-associative A-segment sequential polymerization: Under the conditions of nitrogen protection and reaction temperature, the aqueous solution of A-segment monomer is slowly added dropwise to the reactor. The A-segment monomer is composed of the remaining acrylamide, all 2-acrylamido-2-methylpropanesulfonic acid and all N-octadecylacrylamide. Anhydrous ethanol accounting for 20% of the mass of N-octadecylacrylamide is added to assist in dissolution, and water is added to prepare a homogeneous solution. The dropwise addition time is controlled at 30~45min. After the dropwise addition is completed, the remaining 60%~70% of the redox initiator is added, the system is heated to 33~37℃, and the reaction is maintained for 5~7h to obtain a copolymer product with segmented enrichment characteristics. Among them, the mass part of N-octadecylacrylamide is 2~5 parts, and the mass part of 2-acrylamido-2-methylpropanesulfonic acid is 15~25 parts. (4) Post-processing: The product is cut into 3-5 mm gel particles, extracted with anhydrous ethanol for 8-12 h, vacuum dried at 60-65 °C to constant weight, pulverized and passed through an 80 mesh standard sieve to obtain the dry powder type polymer thickener for coal gas wells.

[0011] Preferably, in step (1), the copolymer is prepared from the following monomers in parts by mass of total monomers: 65 parts acrylamide, 20 parts 2-acrylamide-2-methylpropanesulfonic acid, 10 parts allyl polyoxyethylene ether with a molecular weight of 1200, 3 parts N-octadecylacrylamide, and 2 parts methacrylamide.

[0012] Preferably, in step (1), the B-segment monomer has a mass fraction of 28% in the aqueous solution.

[0013] Preferably, in step (2), the bifunctional water-soluble RAFT reagent is bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate, and the amount used is 0.05% of the total number of monomer moles.

[0014] Preferably, the redox initiator is a combination of ammonium persulfate (APS) and sodium bisulfite.

[0015] Preferably, in step (2), the prepolymerization temperature is 30°C and the reaction time is 2h; in step (3), the polymerization temperature is 35°C and the reaction time is 6h.

[0016] The present invention provides a polymer thickener for coal and rock gas wells, which is prepared by any of the above-described preparation methods.

[0017] The inventive mechanism or principle of this invention is as follows: (1) The viscosity enhancement and shear resistance mechanism of ABA segmented structure Compared to conventional copolymers with randomly distributed monomers, the ABA segmented structure employed in this invention facilitates the relative enrichment of hydrophobic or weakly hydrophobic groups at the chain segment ends or in localized regions, thereby making it easier to form reversible association domains in the aqueous phase. These reversible association domains contribute to the formation of a physical cross-linked network under static or low-shear conditions and can undergo reversible dissociation under high-shear conditions, thus reducing the risk of permanent main chain breakage. When the shear force weakens, the association domains can be re-established, which is beneficial for the recovery of the system's viscosity. Therefore, the ABA segmented design is the structural basis for improving shear resistance and recovery performance.

[0018] (2) Side group-regulated low-temperature dissolution mechanism Conventional polyacrylamide materials may exhibit slower dissolution rates or localized aggregation at low temperatures due to decreased chain mobility and enhanced intermolecular interactions. This invention introduces methacrylamide, whose methyl side groups can, to some extent, alter the chain conformation and local regularity, reduce the tendency for close packing between chains, and help increase the rate at which water molecules enter the particle interior, thereby improving swelling and dissolution behavior under low-temperature conditions.

[0019] (3) Interfacial adsorption and filtration loss reduction mechanism The allyl polyoxyethylene ether side chain introduced in this invention contains multiple ether oxygen atoms. Under conditions where polar sites exist on coal and clay mineral surfaces, it can enhance the polymer's retention and coverage capacity at the reservoir interface through hydrogen bonding, dipole interactions, and interfacial wetting regulation. This interfacial interaction helps improve the polymer's adhesion to the coal surface, reduces the intrusion rate of the liquid phase into deeper reservoirs, and thus improves filtration control. The interfacial adsorption effect is influenced by factors such as salinity, temperature, surface mineral composition, and fluid formulation; the above effects are synergistic.

[0020] 3. Beneficial effects

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses an ABA-type segmented structure design to enrich hydrophobic associative groups at the end of the chain segments to form a reversible physical cross-linking network. After continuous shearing for 120 min at 170 s⁻¹, the viscosity retention rate reaches more than 85%, which is significantly higher than that of conventional random copolymer products (62.3%). Moreover, the viscosity recovery speed after shearing is faster, making it more suitable for large-volume volumetric fracturing conditions. (2) The present invention introduces methacrylamide to regulate the chain segment conformation, improve the low temperature solubility performance, and shorten the dissolution time to 11~14 min at 5℃, which is significantly shorter than the random copolymer product (38 min). In addition, the flocculation phenomenon in the solution is reduced, which is beneficial to rapid solution preparation under low temperature construction conditions. (3) The present invention enhances interfacial adsorption through the side chain of allyl polyoxyethylene ether, thereby reducing the filtration loss. The API filtration loss is reduced to 17.6~19.5 mL / 30 min, which is significantly lower than that of random copolymer products (23.7 mL / 30 min), which helps to reduce liquid phase intrusion and protect the reservoir. (4) The present invention adopts the RAFT controlled polymerization process, and the molecular weight distribution index (PDI) of the product is ≤1.8, which is more concentrated than that of traditional free radical polymerization products (PDI=2.45). The performance fluctuation between batches is small, which is conducive to the stable control of the formulation on site. (5) While improving shear resistance, low-temperature dissolution and filtration loss reduction, the present invention maintains good salt and temperature resistance. Under the condition of total mineralization of 150,000 mg / L, the apparent viscosity still reaches 59~65 mPa·s, indicating that the introduction of 2-acrylamide-2-methylpropanesulfonic acid and the segmented structure design have a positive effect on the salt and temperature resistance of the system. (6) The preparation process of this invention is controllable, the product performance is synergistically improved, and it is easy to prepare industrially. Attached Figure Description

[0022] Figure 1 This is a process flow diagram of a polymer thickener for coal and rock gas wells and its preparation method according to the present invention; Figure 2This is a schematic diagram of the ABA-type segmented polymer structure of the present invention; wherein the middle segment is segment B (hydrophilic flexible segment), and both ends are segments A (hydrophobic associative segments), x, y, and z represent the relative number of monomer units in each segment, x and z > 0, and y is the main chain segment; Figure 3 GPC comparison chart of the ABA-type segmented polymer and the B-segment prepolymer of the present invention: original effluent curves (RI detection); Figure 4 GPC comparison diagram of the ABA-type segmented polymer and the B-segment prepolymer of the present invention: differential molecular weight distribution curve; Figure 5 The ¹H NMR spectra of the ABA-type segmented polymer and the B-segment prepolymer of the present invention are compared. Detailed Implementation

[0023] The more detailed description of embodiments of the invention below is not intended to limit the scope of the claimed invention, but is merely illustrative and does not limit the description of the features and characteristics of the invention, in order to suggest the best mode for carrying out the invention and to enable those skilled in the art to practice the invention. However, it should be understood that various modifications and variations can be made without departing from the scope of the invention as defined by the appended claims. The detailed description should be considered illustrative only and not restrictive, and any such modifications and variations shall fall within the scope of the invention described herein. Furthermore, the background art is intended to illustrate the current state of research and development and significance of the technology, and is not intended to limit the invention or the scope of application of this application.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention.

[0025] The performance testing of this invention is conducted in accordance with SY / T 5107-2016 "Performance Evaluation Method for Water-Based Fracturing Fluids", and the specific testing methods are as follows: 1. Apparent viscosity: Measured using a six-speed rotational viscometer at 170 s⁻¹ and 25°C, with a thickener addition of 0.3%; 2. Shear retention rate: After continuous shearing for 120 min at 170 s⁻¹, the ratio of the sample viscosity to the initial viscosity was measured; 3. Low-temperature dissolution time: Under constant temperature water bath conditions of 5℃ and stirring at 300rpm, observe the time it takes for the sample to dissolve until no visible flocs are visible; 4. API filtration loss: Measure the static filtration loss over 30 minutes at room temperature; 5. Salt resistance viscosity: A 0.3% solution was prepared using simulated formation water with a total mineralization of 150,000 mg / L and calcium and magnesium ions of 1,000 mg / L, and its apparent viscosity was measured. 6. Molecular weight distribution index: determined by gel permeation chromatography (GPC).

[0026] The present invention will be further described below with reference to specific embodiments.

[0027] Example 1 This embodiment provides a method for preparing a polymer thickener for coal and rock gas wells. It employs a bifunctional water-soluble RAFT reagent combined with a sequential two-step aqueous solution polymerization process to prepare a water-soluble copolymer with an ABA-type segmented structure. The middle B segment is a flexible hydrophilic segment, while the two end A segments are hydrophobic or weakly hydrophobic segments rich in associating groups. The copolymer is prepared from the following monomers in parts by mass: 65 parts acrylamide, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 10 parts allyl polyoxyethylene ether with a molecular weight of 1200, 3 parts N-octadecylacrylamide, and 2 parts methacrylamide. The method includes the following steps: (1) Preparation and deoxygenation of reaction system: Weigh 42.25 parts (65×0.65=42.25) of the monomers in section B, namely 65% ​​of the total monomers, 10 parts of all-allyl polyoxyethylene ether and 2 parts of all-methacrylamide, add them to deionized water and stir until completely dissolved to prepare an aqueous solution with a monomer mass fraction of 28% in section B; adjust the pH of the system to 7.0 with a sodium hydroxide solution with a mass fraction of 20%; transfer the aqueous phase into a sealed reaction vessel with a jacket and temperature control, and introduce high-purity nitrogen gas to deoxygenate for 25 min, maintaining a slight positive pressure of nitrogen gas (0.04 MPa). (2) Flexible hydrophilic B-segment prepolymerization: Bifunctional water-soluble RAFT reagent bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate was added to the reactor, with an amount of 0.05% of the total monomer molars; the system temperature was controlled at 30℃, and a redox initiator consisting of ammonium persulfate and sodium bisulfite (molar ratio 1:1) was added. The amount of the first part of the initiator was 35% of the total initiator mass, and the amount of the total initiator was 0.02% of the total monomer mass; the reaction was kept at the temperature for 2h to obtain a B-segment prepolymer with chain end activity characteristics; (3) Hard-associative A-segment sequential polymerization: Under the conditions of nitrogen protection and reaction temperature, the aqueous solution of A-segment monomer is slowly added dropwise to the reactor; the A-segment monomer is composed of 22.75 parts of the remaining acrylamide, 20 parts of all 2-acrylamido-2-methylpropanesulfonic acid and 3 parts of all N-octadecylacrylamide, and 0.6 parts of anhydrous ethanol accounting for 20% of the mass of N-octadecylacrylamide is added to assist in dissolution, and then water is added to prepare a homogeneous solution; the dropwise addition time is controlled at 35 min; after the dropwise addition is completed, the remaining 65% of the redox initiator is added, the system is heated to 35℃, and the reaction is kept at the temperature for 6 h to obtain a copolymer product with segmented enrichment characteristics; (4) Post-processing: After the product is taken out, it is cut into 4mm granules by a granulator, then extracted with anhydrous ethanol for 10h by Soxhlet extraction, and dried under vacuum at 63℃ to constant weight. After being crushed and passed through an 80-mesh standard sieve, the dry powder type polymer thickener for coal gas wells is obtained.

[0028] The performance test results of the polymer thickener for coal and rock gas wells prepared in this embodiment are summarized in Tables 1, 2 and 3.

[0029] Example 2 This embodiment provides a method for preparing a polymer thickener for coal and rock gas wells. It employs a bifunctional water-soluble RAFT reagent combined with a sequential two-step aqueous solution polymerization process to prepare a water-soluble copolymer with an ABA-type segmented structure. The copolymer is prepared from the following monomers in parts by mass: 70 parts acrylamide, 18 parts 2-acrylamido-2-methylpropanesulfonic acid, 7 parts allyl polyoxyethylene ether with a molecular weight of 1200, 3.5 parts N-octadecylacrylamide, and 1.5 parts methacrylamide. The method includes the following steps: (1) Preparation and deoxygenation of reaction system: Weigh 47.6 parts (70×0.68=47.6) of the monomers in section B, namely 68% of the total monomers, acrylamide, 7 parts of all-allyl polyoxyethylene ether, and 1.5 parts of all-methacrylamide. Add them to deionized water and stir until completely dissolved to prepare an aqueous solution with a total monomer mass fraction of 25%. Adjust the pH of the system to 6.8 with a sodium hydroxide solution with a mass fraction of 20%. Transfer the aqueous phase into a closed reaction vessel with a jacket and temperature control, and introduce high-purity nitrogen gas to deoxygenate for 25 min, maintaining a slight positive pressure of nitrogen gas (0.01 MPa). (2) Flexible hydrophilic B-segment prepolymerization: Bifunctional water-soluble RAFT reagent bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate was added to the reactor, with an amount of 0.03% of the total monomer molars; the system temperature was controlled at 28℃, and a redox initiator consisting of ammonium persulfate and sodium bisulfite (molar ratio 1:1) was added. The amount of the first part of the initiator was 30% of the total initiator mass, and the amount of the total initiator was 0.02% of the total monomer mass; the reaction was kept at the temperature for 2.5h to obtain a B-segment prepolymer with chain end activity characteristics; (3) Hard-associative A-segment sequential polymerization: Under the conditions of nitrogen protection and reaction temperature, the aqueous solution of A-segment monomer is slowly added dropwise to the reactor; the A-segment monomer is composed of 22.4 parts of the remaining acrylamide, 18 parts of all 2-acrylamido-2-methylpropanesulfonic acid and 3.5 parts of all N-octadecylacrylamide, and 0.7 parts of anhydrous ethanol accounting for 20% of the mass of N-octadecylacrylamide is added to assist dissolution, and then water is added to prepare a homogeneous solution; the dropwise addition time is controlled at 30 min; after the dropwise addition is completed, the remaining 70% of the redox initiator is added, the system is heated to 33℃, and the reaction is kept at the temperature for 7 h to obtain a copolymer product with segmented enrichment characteristics; (4) Post-processing: After the product is taken out, it is cut into 3mm granules by a granulator, then extracted with anhydrous ethanol for 8 hours, and vacuum dried at 60℃ to constant weight. After being crushed and passed through an 80-mesh standard sieve, the dry powder type polymer thickener for coal gas wells is obtained.

[0030] The performance test results of the polymer thickener for coal and rock gas wells prepared in this embodiment are summarized in Tables 1, 2 and 3.

[0031] Example 3

[0032] This embodiment provides a method for preparing a polymer thickener for coal and rock gas wells. It employs a bifunctional water-soluble RAFT reagent combined with a sequential two-step aqueous solution polymerization process to prepare a water-soluble copolymer with an ABA-type segmented structure. The copolymer is prepared from the following monomers in parts by mass: 60 parts acrylamide, 24 parts 2-acrylamido-2-methylpropanesulfonic acid, 11 parts allyl polyoxyethylene ether with a molecular weight of 1200, 3 parts N-octadecylacrylamide, and 2 parts methacrylamide. The method includes the following steps: (1) Preparation and deoxygenation of reaction system: Weigh 42 parts (60×0.70=42) of acrylamide (70% of total monomer content), 11 parts of all-allyl polyoxyethylene ether, and 2 parts of all-methacrylamide. Add them to deionized water and stir until completely dissolved to prepare an aqueous solution with a total monomer mass fraction of 30%. Adjust the pH of the system to 7.2 with a 20% sodium hydroxide solution. Transfer the aqueous phase to a sealed reaction vessel with a jacket and temperature control. Purge with high-purity nitrogen for 25 min to remove oxygen and maintain a slight positive pressure of nitrogen (0.05 MPa). (2) Flexible hydrophilic B-segment prepolymerization: Bifunctional water-soluble RAFT reagent bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate was added to the reactor, with an amount of 0.08% of the total monomer molars; the system temperature was controlled at 32℃, and a redox initiator consisting of ammonium persulfate and sodium bisulfite (molar ratio 1:1) was added. The amount of the first part of the initiator was 40% of the total initiator mass, and the amount of the total initiator was 0.02% of the total monomer mass; the reaction was kept at the temperature for 1.5h to obtain a B-segment prepolymer with chain end activity characteristics; (3) Hard-associative A-segment sequential polymerization: Under the conditions of nitrogen protection and reaction temperature, the aqueous solution of A-segment monomer is slowly added dropwise to the reactor; the A-segment monomer is composed of 18 parts of the remaining acrylamide, 24 parts of all 2-acrylamido-2-methylpropanesulfonic acid and 3 parts of all N-octadecylacrylamide, and 0.6 parts of anhydrous ethanol accounting for 20% of the mass of N-octadecylacrylamide is added to assist in dissolution, and then water is added to prepare a homogeneous solution; the dropwise addition time is controlled at 45 min; after the dropwise addition is completed, the remaining 60% of the redox initiator is added, the system is heated to 37°C, and the reaction is kept at the temperature for 5 h to obtain a copolymer product with segmented enrichment characteristics; (4) Post-processing: After the product is taken out, it is cut into 5mm granules by a granulator, then extracted with anhydrous ethanol for 12h by Soxhlet extraction, and dried under vacuum at 65℃ to constant weight. After being crushed and passed through an 80-mesh standard sieve, the dry powder type polymer thickener for coal gas wells is obtained.

[0033] The performance test results of the polymer thickener for coal and rock gas wells prepared in this embodiment are summarized in Tables 1, 2 and 3.

[0034] Comparative Example 1 (Conventional random copolymer, same monomer ratio) This comparative example provides a method for preparing a polymer tackifier. The main difference between this comparative example and Example 1 is that it uses the same monomer ratio as Example 1 (65 parts acrylamide, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 10 parts allyl polyoxyethylene ether (molecular weight 1200), 3 parts N-octadecylacrylamide, and 2 parts methacrylamide), and is prepared by conventional free radical aqueous solution polymerization. All monomers are added at once, and after nitrogen purging to remove oxygen, all initiators are added at once. The reaction is carried out at 35°C for 8 hours, and the post-treatment is the same as in Example 1. That is, the ABA segmented structure design and RAFT controlled polymerization process are not used.

[0035] The performance test results of the polymer tackifiers prepared in this comparative example are summarized in Tables 1, 2 and 3.

[0036] Comparative Example 2 (without the regularity-regulating monomer methacrylamide) This comparative example provides a method for preparing a polymer tackifier. The main difference between this comparative example and Example 1 is that: methacrylamide is removed from the monomers, and acrylamide is used to make up the mass (i.e., the amount of acrylamide is 67 parts, 2-acrylamido-2-methylpropanesulfonic acid is 20 parts, allyl polyoxyethylene ether (molecular weight 1200) is 10 parts, and N-octadecylacrylamide is 3 parts), while the remaining proportions and polymerization process are the same as in Example 1. That is, it does not contain methyl side group regulating units.

[0037] The performance test results of the polymer tackifiers prepared in this comparative example are summarized in Tables 1, 2 and 3.

[0038] Comparative Example 3 (without the interface-reinforcing monomer allyl polyoxyethylene ether) This comparative example provides a method for preparing a polymer tackifier. The main difference between this comparative example and Example 1 is that the allyl polyoxyethylene ether in the monomer is removed, and the mass is made up with acrylamide (i.e., the amount of acrylamide is 75 parts, 2-acrylamido-2-methylpropanesulfonic acid is 20 parts, N-octadecylacrylamide is 3 parts, and methacrylamide is 2 parts). The remaining proportions and polymerization process are the same as in Example 1. That is, it does not contain polyoxyethylene ether interface reinforcing side chains.

[0039] The performance test results of the polymer tackifiers prepared in this comparative example are summarized in Tables 1, 2 and 3.

[0040] Performance Testing and Comparison

[0041] The performance of the polymer thickeners for coal gas wells prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are as follows: The performance of the polymer thickeners for coal gas wells prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are as follows: Table 1 Comparison of test results for thickening and shear resistance Initial apparent viscosity (mPa·s) 85 82 88 76 83 79 Viscosity retention rate (%) after 120 min of shearing 87.2 85.6 89.1 62.3 86.1 85.8 Table 2 Comparison of test results for low-temperature dissolution and filtration loss reduction performance Dissolution time at 5℃ (min) 12 14 11 38 35 13 API filtration loss (mL / 30min) 18.2 19.5 17.6 23.7 18.5 24.1 Table 3 Comparison of Salt Tolerance and Molecular Weight Distribution Test Results Apparent viscosity (mPa·s) at high mineralization 62 59 65 51 60 58 Molecular weight distribution index (PDI) 1.62 1.71 1.58 2.45 1.65 1.60 In summary, as can be seen from Tables 1-3: (1) Compared with Comparative Example 1 (conventional random copolymerization), Examples 1-3 showed a significant improvement in shear retention rate (85.6%~89.1% vs 62.3%), indicating that the ABA segmented structure design enabled the segmented enrichment of associating groups, effectively constructing a reversible physical cross-linking network and improving shear resistance and recovery performance. At the same time, the examples showed significant improvement in low-temperature dissolution rate and filtration loss control, indicating that the segmented structure, side group regulation and the introduction of interfacial monomers have a synergistic effect.

[0042] (2) Compared with Comparative Example 2 (without methacrylamide), the low-temperature dissolution time of Example 1 (12 min) was much shorter than that of Comparative Example 2 (35 min), indicating that the methyl side group has a significant regulatory effect on the low-temperature dissolution behavior; while the shear retention rate was similar (87.2% vs 86.1%), indicating that the introduction of methacrylamide had almost no effect on the shear resistance of the ABA segmented structure.

[0043] (3) Compared with Comparative Example 3 (without allyl polyoxyethylene ether), the API filtration loss of Example 1 (18.2 mL / 30 min) was significantly lower than that of Comparative Example 3 (24.1 mL / 30 min), indicating that the polyoxyethylene ether side chain has a positive contribution to interfacial interaction and filtration loss reduction performance; while the shear retention rate and low temperature dissolution time were similar, indicating that the introduction of allyl polyoxyethylene ether does not affect other properties.

[0044] (4) Each embodiment still maintains an apparent viscosity of 59~65 mPa·s under high salinity conditions, which is significantly higher than that of Comparative Example 1 (51 mPa·s), indicating that the contribution of 2-acrylamide-2-methylpropanesulfonic acid to salt resistance is stable and that the segmented ABA structure design does not significantly weaken its salt resistance advantage.

[0045] (5) The PDI of Examples 1 to 3 was 1.58 to 1.71, which was much lower than that of Comparative Example 1 (2.45), indicating that the RAFT controlled polymerization process effectively controlled the molecular weight distribution, which is beneficial to improving the batch stability of the product.

[0046] To further verify the successful synthesis of the ABA copolymer in this invention, the applicant repeated the preparation process of Example 3 and characterized it using a combination of gel permeation chromatography (GPC) and ¹H NMR spectroscopy, referring to... Figures 3-5 The specific analysis and discussion are as follows, along with Table 4: Table 4. Comparison of GPC numerical results Mn (g / mol) 8620 36800 Mw (g / mol) 12450 56900 PDI (Mw / Mn) 1.44 1.55 Mp (g / mol) 10200 42300 like Figure 3 and Figure 4As shown, GPC test results indicate that, compared to the hydrophilic prepolymer of segment B, the peak position of the original elution curve of the final ABA block copolymer shifts significantly to the left towards shorter retention times. The slightly lower ABA peak intensity may be due to differences in injection concentration and refractive index increment (dn / dc). The differential molecular weight distribution curve shifts significantly towards higher molecular weights. Referring to Table 4, the corresponding molecular weight parameters show that the number-average molecular weight Mn increased from 8620 g / mol to 36800 g / mol, the weight-average molecular weight Mw increased from 12450 g / mol to 56900 g / mol, the peak molecular weight Mp increased from 10200 g / mol to 42300 g / mol, and the molecular weight distribution index PDI increased slightly from 1.44 to 1.55 (the slight difference from 1.58 in Example 3 is due to the error range of repeated experiments). It maintains a narrow single-peak distribution throughout, and there are no obvious low-molecular-weight prepolymer residual peaks in the product curve. The results indicate that the polymer molecular weight was significantly and uniformly increased after the polymerization reaction, and there were no large amounts of unreacted B-segment prepolymers or homopolymerized A-segment byproducts. This directly proves that the A-segment monomers were successfully grafted onto the reaction sites of the B-segment prepolymers, forming a high molecular weight block polymer.

[0047] ¹H NMR spectra further verified the structural correctness at the molecular functional group level: the characteristic peak of the side chain vinyl group at ~5.6 ppm in the B-segment prepolymer almost completely disappeared in the final product, proving that the double bond had fully participated in the polymerization reaction; the ~6.8 ppm peak was formamide, with no significant difference; the product spectrum showed the addition of a long alkyl methylene characteristic peak at ~1.2 ppm and a main chain characteristic peak of the N-sulfonacrylamide unit at ~2.6 ppm, confirming that the long alkyl hydrophobic unit and the sulfonated functional unit in segment A had been successfully introduced; at the same time, the characteristic peak of the polyoxyethylene chain at ~3.4-3.8 ppm was stably retained, indicating that the main framework of the hydrophilic flexible chain in segment B remained intact during the polymerization process and did not undergo degradation.

[0048] Based on the molecular weight distribution evidence from GPC and the functional group structure evidence from ¹H NMR, it can be confirmed that an ABA-type triblock copolymer with hydrophobic A segments at both ends and a hydrophilic flexible B segment in the middle was successfully prepared through two-step polymerization. The product structure is completely consistent with the design target.

[0049] The present invention has been described in detail above with reference to specific exemplary embodiments. However, it should be understood that various modifications and variations can be made without departing from the scope of the invention as defined by the appended claims. The detailed description should be considered illustrative only and not restrictive, and any such modifications and variations shall fall within the scope of the invention described herein. Furthermore, the background art is intended to illustrate the current state of development and significance of the technology and is not intended to limit the present invention or the scope of application of the present application.

[0050] More specifically, although exemplary embodiments of the invention have been described herein, the invention is not limited to these embodiments, but includes any and all embodiments modified, omitted, such as combinations between various embodiments, adaptive changes, and / or substitutions, as would be apparent to those skilled in the art from the foregoing detailed description. The limitations in the claims are to be interpreted broadly as used in the language of the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of this application, which should be considered non-exclusive. Any step listed in any method or process claim may be performed in any order and is not limited to the order set forth in the claims. Therefore, the scope of the invention should be determined solely by the appended claims and their legal equivalents, and not by the description and examples given above.

[0051] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In case of conflict, the definitions in this specification shall prevail. When flow rate, power, refractive index, time, or other values ​​or parameters are expressed as ranges, preferred ranges, or a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether such range is disclosed individually. For example, the range 1-50 should be understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, as well as all decimal values ​​between the integers mentioned above, such as 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. Regarding subranges, specifically consider "nested subranges" extending from any endpoint of the range. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30 and 1-40 in one direction, or 50-40, 50-30, 50-20 and 50-10 in another direction.

Claims

1. A method for preparing a polymer thickener for coal and rock gas wells, characterized in that, A water-soluble copolymer with ABA-type segmented structure was prepared by using a bifunctional water-soluble RAFT reagent combined with a sequential two-step aqueous solution polymerization process. The middle B segment is a flexible hydrophilic segment, and the two A segments at both ends are hydrophobic or weakly hydrophobic segments enriched with associating groups. The preparation method includes the following steps: (1) Preparation and deoxygenation of reaction system: Weigh out the monomers of section B according to the ratio, namely 65%~75% of the total monomer amount of acrylamide, all allyl polyoxyethylene ether and all methacrylamide, add them to deionized water and stir until completely dissolved to prepare an aqueous solution with a total monomer mass fraction of 25%~30%; adjust the pH of the system to 6.5~7.5 with a 20% sodium hydroxide solution; transfer the aqueous phase into a closed reaction vessel with a jacket and temperature control, and introduce high-purity nitrogen to deoxygenate for 20~30 min, maintaining a slight positive pressure of nitrogen; wherein, the total mass of acrylamide is 60~70 parts, the mass of allyl polyoxyethylene ether is 5~12 parts and the molecular weight is 800~2000, the mass of methacrylamide is 1~3 parts, and the slight positive pressure of nitrogen is 0.01~0.05 MPa; (2) Flexible hydrophilic B-segment prepolymerization: Add a bifunctional water-soluble RAFT reagent to the reactor, the amount of which is 0.03%~0.08% of the total monomer molars. Control the system temperature at 28~32℃. Add the first part of the redox initiator, the amount of which is 30%~40% of the total initiator mass. The total initiator amount is 0.02% of the total monomer mass. Keep the reaction at the temperature for 1.5~2.5h to obtain a B-segment prepolymer with chain end activity characteristics. The bifunctional water-soluble RAFT reagent is bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate. (3) Hard-associative A-segment sequential polymerization: Under the conditions of nitrogen protection and reaction temperature, the aqueous solution of A-segment monomer is slowly added dropwise to the reactor. The A-segment monomer is composed of the remaining acrylamide, all 2-acrylamido-2-methylpropanesulfonic acid and all N-octadecylacrylamide. Anhydrous ethanol accounting for 20% of the mass of N-octadecylacrylamide is added to assist in dissolution, and water is added to prepare a homogeneous solution. The dropwise addition time is controlled at 30~45min. After the dropwise addition is completed, the remaining 60%~70% of the redox initiator is added, the system is heated to 33~37℃, and the reaction is maintained for 5~7h to obtain a copolymer product with segmented enrichment characteristics. Among them, the mass part of N-octadecylacrylamide is 2~5 parts, and the mass part of 2-acrylamido-2-methylpropanesulfonic acid is 15~25 parts. (4) Post-processing: The product is cut into 3-5 mm gel particles, extracted with anhydrous ethanol for 8-12 h, vacuum dried at 60-65 °C to constant weight, pulverized and passed through an 80 mesh standard sieve to obtain the dry powder type polymer thickener for coal gas wells.

2. The method for preparing the polymer thickener for coal and rock gas wells according to claim 1, characterized in that: The copolymer is prepared from the following monomers in parts by mass of total monomers: 65 parts acrylamide, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 10 parts allyl polyoxyethylene ether with a molecular weight of 1200, 3 parts N-octadecylacrylamide, and 2 parts methacrylamide.

3. The method for preparing the polymer thickener for coal and rock gas wells according to claim 1, characterized in that: In step (1), the B-segment monomer has a mass fraction of 28% in the aqueous solution.

4. The method for preparing the polymer thickener for coal and rock gas wells according to claim 1, characterized in that: In step (2), the amount of the bifunctional water-soluble RAFT reagent is 0.05% of the total number of monomer moles.

5. The method for preparing the polymer thickener for coal and rock gas wells according to claim 1, characterized in that: The redox initiator is a combination of ammonium persulfate and sodium bisulfite.

6. The method for preparing the polymer thickener for coal and rock gas wells according to claim 1, characterized in that: In step (2), the prepolymerization temperature is 30℃ and the reaction time is 2h; in step (3), the polymerization temperature is 35℃ and the reaction time is 6h.

7. A polymer thickener for coal and rock gas wells, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Dispersing agent containing composite long-short side chain polycarboxylate and RAFT (Reversible Addition-Fragmentation chain Transfer) synthesis method of aqueous solution thereof

    CN107828061A

  • Method for preparing degradable polyacrylamide fracturing fluid by RAFT (reversible addition-fragmentation chain transfer) polymerization method

    CN119875006A